Implementation of Law Number 12 Of 2022 Concerning Criminal Acts of Sexual Violence in Public Transportation - Andriyani, Adinda Zahra; Mulyadi, Mulyadi (Dinasti Research, 2025)
This study examines the implementation of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence in the context of public transportation in Indonesia. The background to this research is based on the high number of cases of sexual violence in public spaces, particularly public transportation, which creates a sense of insecurity for women and vulnerable groups. This study aims to analyze the application of the provisions of the TPKS Law to criminal acts of sexual violence in public transportation and identify obstacles faced in its implementation. The research method used is normative juridical with a legislative, conceptual, and case-based approach. The results show that although the TPKS Law provides a comprehensive legal basis and guarantees victim-based protection, its implementation remains limited in effectiveness. The main obstacles include difficulties in providing evidence, incomplete implementing regulations, limited understanding of the substance of the law by officials, and the strong patriarchal culture and practices of victim blaming in society. Therefore, synergy is needed between the government, law enforcement officials, transportation operators, and the community to strengthen the implementation of the TPKS Law so that the law's main objective of creating a safe public space free from sexual violence can be realized.